Techno-economic Analysis of MEA CO2 Capture from a Cement Kiln – Impact of Steam Supply Scenario. (July 2017) - Roussanaly, Simon; Fu, Chao; Voldsund, Mari; Anantharaman, Rahul; Spinelli, Maurizio; Romano, Matteo
Abstract: This paper present the techno-economic assessment of an MEA-based CO2 capture from a cement plant and the importance of the steam supply on the costs. The evaluations present the energy performances of the CO2 capture process based on a cement plant with a clinker capacity of 3, 000 t/d. The cost evaluation lead to a cost of cement of 45 €/tcement without capture, while the cost of cement with CO2 capture is estimated to 81 €/tcement, resulting in a CO2 avoided cost of 83 €/tCO2, avoided . As the steam consumption accounts for close to half of the CO2 avoided cost, the impact of six alternative steam supply scenarios are considered. The evaluations show that the CO2 avoided cost can decrease by up to 35% depending on the steam supply and electricity price. However the possibility of these steam supply alternatives are specific to the considered cement plant, emphasizing therefore that CO2 avoided cost from cement shall rather be given as a range depending on the steam supply than as a unique value as often illustrated in the literature.